Clinical profile and psychiatric comorbidity of treatment seeking individuals with pathological gambling in South Africa. - Sinclair, Heidi (Department of Psychiatry and Mental Health, 2024)
Background: Pathological gambling is a prevalent and disabling mental illness, which is frequently associated with mood, anxiety, and substance use disorders. However, there is relatively little data on comorbidity in individuals with pathological gambling from low and middle income countries such as South- Africa. Method: The Mini-International Neuropsychiatric Interview (MINI) was used to assess the frequency of DSM-IV-TR disorders among 100 male and 100 female treatment-seeking individuals with pathological gambling in South-Africa. The Sheehan Disability Scales were used to assess functional impairment. Results: : In a South-African sample of individuals with pathological gambling, the most frequent current comorbid psychiatric disorders were major depressive disorder (28%), anxiety disorders (25.5%) and substance use disorders (10.5%). Almost half of the individuals had a lifetime diagnosis of major depressive disorder (46%). Female pathological gamblers were significantly more likely to be diagnosed with a comorbid major depressive disorder or generalised anxiety disorder than their male counterparts. Conclusions: Data from South-Africa are consistent with previously published data from high income countries. Psychiatric comorbidity is common among individuals with pathological gambling.